Spark - Kemmerer, Brigid (Kemmerer, Brigid. Elemental series., 2012)
"Gabriel Merrick plays with fire. Literally. Sometimes he can even control it. And sometimes he can't. Gabriel has always had his brothers to rely on, especially his twin, Nick. But when an arsonist starts wreaking havoc on their town, all the signs point to Gabriel. Only he's not doing it. And no one seems to believe him. Except a shy sophomore named Layne, a brainiac who dresses in turtlenecks and jeans and keeps him totally off balance. Layne understands family problems, and she understands secrets. She has a few of her own"--backcover.